On the Dual Nature of Sem-Phrases in Hungarian: Negative Quantifiers or Negative Indefinites? - Dalmi, Gréte (Linguistic Exploration, 2026)
Sem-phrases in Hungarian are negative indefinites accompanied by the negative emphatic particle sem ‘neither’. Preverbal sem-phrases differ from postverbal ones in that the former behave as negative quantifiers (NQs), while the latter resemble s-words, which are negative concord items (NCIs) like senki ‘nobody’. By adopting Ladusaw’s distinction between syntactic vs. semantic licensing, the paper offers an explanation for this variation in a purely cartographic syntactic framework. Earlier accounts turned around the universal vs. existential interpretations of negative indefinites. The present proposal derives the interpretive differences from their different licensing requirements. It extends the proposed analysis to negative connectives, where nominals precede sem ‘neither’, and negative conjunction constructions, where nominals follow sem ‘neither’. Preverbal nominals show quantificational properties only when they precede sem ‘neither’; postverbally, however, the same nominals are non-quantificational NCIs. Nominals following sem ‘neither’ are invariably NCIs. Therefore, a uniform quantificational analysis for all these items is untenable. Finally, the paper briefly discusses (még) ... sem ‘not ... even’ constructions with nominals modified by numerical quantifiers and classifiers, which mimic the behaviour of sem-phrases and nominals accompanied by sem ‘neither’ in preverbal and postverbal positions. All these differences follow from a special freezing effect called Criterial Freezing, which applies whenever the specifier of the SEMP functional projection is filled.